HOW TO TEACH WRITING IN LITERATURE CLASS THROUGH GENRE-BASED APPROACH - FIFTINOVA, FIFTINOVA
This present study was conducted in order to portray how to teach writing inliterature class throgh Genre-Based Approach. Specifically, this study identifies (1)how lecturer guides students write their response to literature through Genre-BasedApproach, and (2) how the students write their response to literature using Genre-Based Approach. Qualitative case study design was chosen as the method of thestudy. The participants were 1 lecturer and 40 students who studied Prose in EnglishEducation Study Program at one state university in Palembang. The data werecollected through observation, documentation, and questionnaire. The data wereanalyzed qualitatively by doing thematic analysis. The result shows that (1) all theprocedures of Genre-Based Approach which incorporated Building Knowledge ofThe Field (BKOF), Modelling, Joint Construction and Independent writing werehelpful in facilitating students writing, specifically BKOF and Joint Construction;(2) Most of the participants, to some extents, have applied the schematic structures(introduction, expands-on and summary) and the linguistic features modeled in thisstudy.